2015
DOI: 10.1682/jrrd.2014.10.0243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kinesio Tape application to quadriceps muscles on isokinetic muscle strength, gait, and functional parameters in patients with stroke

Abstract: Abstract-The aim of this study was to evaluate the effects of Kinesio Tape (KT) application to quadriceps muscles on isokinetic muscle strength, gait, and functional parameters in patients with stroke. Twenty-four patients were allocated into KT and control groups. All patients participated in the same conventional rehabilitation program 5 times/wk for 4 wk. In addition, KT was applied to quadriceps muscles bilaterally to the patients in the KT group. Compared with baseline, peak torque levels increased signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 19 publications
1
33
0
2
Order By: Relevance
“…According to Boguszewski et al [20], taping applied to healthy adults significantly augmented the activation and strength of lower-extremity muscles. Furthermore, Ekiz et al [15] and Kim et al [12] found an increase in walking speed after taping of stroke patients in a 10-meter walking test. Thus, previous studies have shown that taping improved muscle strength and functional movement along with ankle stability and muscle activation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…According to Boguszewski et al [20], taping applied to healthy adults significantly augmented the activation and strength of lower-extremity muscles. Furthermore, Ekiz et al [15] and Kim et al [12] found an increase in walking speed after taping of stroke patients in a 10-meter walking test. Thus, previous studies have shown that taping improved muscle strength and functional movement along with ankle stability and muscle activation.…”
Section: Discussionmentioning
confidence: 95%
“…For the rectus femoris muscle, the tape was applied from 10 cm below the anterior superior iliac spine to the superior edge of the patella (without tension). The tape was then crossed from the edges of the patella (with maximum tension) and fixed below the inferior edge of the patella while the knee was flexed [15]. For the gluteus maximus muscle, two Y-shaped pieces of tape (approximately 35 cm long and 5 cm wide) were applied with the tails of the Y being 30 cm long and 2.5 cm wide, leaving a base of 5 cm, which is the estimated distance between the participant's greater trochanter and fifth lumber (L5) spinous process [16] ( Figure 1).…”
Section: Design and Settingmentioning
confidence: 99%
“…Measurements of 10-meter walking speed were taken before treatment and on the first and third days, and it was concluded that the application of KT increased walking speed. Ekiz et al 14 applied KT to the quadriceps muscle of stroke patients and determined no significant increase in walking speed after treatment compared to the control group. Furthermore, in a study of 11 basketball players, Wohltman 15 determined a positive effect of KT treatment on walking speed.…”
Section: Kt (N=31) Sham-kt (N=30)mentioning
confidence: 99%
“…Of these, 732 studies were excluded after reading the titles, 22 after reading the summaries and 5 after reading the full text. Manual search did not return any item and thus the final number of studies included in this study was 15 14,15,[19][20][21][22][23][24][25][26][27][28][29][30][31] . The main reason for exclusion of studies were: use of animals, use of medication, studies in clinical conditions other than CVA in and studies with types of intervention other than the KT.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%